It Probably Works. - MCMULLEN, TYLER (Communications of the ACM, 2015)
The article discuss probabilistic algorithms used in problem solving, focusing on those that introduce randomness through a rand() call and those that convert input data into a uniform distribution. Noted algorithms that are categorized as such include LogLog, HyperLogLog, and Bimodal Multicast.